Peningkatan Keterampilan Menulis Cerita Di SDN Cikalang Menggunakan Bahan Ajar Lift The Flap Book - Delia Maharani (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2023)
Writing skills are a skill on which the text is carried on. Writing also has the advantage of being an indirect means of communication but only one - way communication between the writer and his reader. The flap book's lift leads to a teaching based on the creation of interactive illustrated books, and it has pictures and texts in it by means of a paper technique that can close or can be referred to by a windowless book. The purpose of this study is to know the increasing skill of writing the story from the flap book of the class iii students in the teachers' swing. The approach used in this study is a quantitative approach using a type of experimental design quasi with a non-invasive control group design. The design has two randomly selected groups, each given the same treatment in pretests, treatment and posttests. The study subject is a class iii student of 52 children with details of 26 children as an experiment group and 26 children as a control group. The validity of the instrument using brivate Pearson. The data collection technique used is the tests and observations used to measure the students' storywriting skills. The normality and homogenity tests Shared colmogorov snov and the levene test for equality. Hypothetical testing USES the independent formula of t-test samples with help SPSS 15 for Windows with value value < 0.05. Hypothetical testing identified the value of sig. (2-tailed) by 0.004 < 0.05, the basis for decision-making in the independent test of t-tests can be concluded that there is a significant and correct difference between the experimental group and the control group. Experimental groups get a much higher value increase compared with the control group. The experimental group with a 10/15 27 pretest while its posttest scores rose to 14.08. The control group pretest scores 10.12 while its posttest scores are 12.23. This proves that the flap book's elevator teaching materials can provide an increased listening skill for class iii students. With the use of the flap book's lift, students are able to re-foster students' attention, interest, and creativity in learning, sharpening and getting used to storywriting skills.